WHAT IS THE KNOWLEDGE OF ELEMENTARY SCHOOL TEACHERS ABOUT SCOLIOSIS? - ANDERSON ALVES DIAS; MARCOS VINICIUS LAZARINI DA CUNHA; LEONARDO FRANCO PINHEIRO GAIA; NÍCOLAS SANTOS DE OLIVEIRA; ANDRÉA LICRE PESSINA GASPARINI; ISABEL APARECIDA PORCATTI DE WALSH; DERNIVAL BERTONCELLO (Acta Ortopédica Brasileira, 2023)
ABSTRACT Objective: To evaluate the knowledge about scoliosis in teachers of municipal public schools. Methods: In total, 126 professionals were interviewed using a standard questionnaire containing issues related to scoliosis. Results: 31% of interviewees did not know what scoliosis is. Of those who knew 89.65% were partially correct about the definition. Of those who claimed to know how the scoliosis diagnosis is made, only 25.58% were completely correct. When questioned about the Adams test, 84.9% did not know it. Among the interviewees, 57.9% answered that it is impossible to identify scoliosis by a simple examination of their students and, off these, 86.3% stated the lack of knowledge about the subject; and 92.1% considered that training for the diagnosis and early identification of scoliosis in students. Conclusion: This study holds social impact since the interviewed teachers were not knowledgeable about the subject and had difficulty in providing a definition of the condition and in how to proceed with the investigation. Continuous education activities and the inclusion of this subject on the curricula of teacher education programs would improve the early diagnosis and treatment of scoliosis, with high success rates. Level of Evidence IV, Economic and Decision Analyses.